Applying C-13 techniques in exploring the carbon sequestration potential of limed acid soils fromt Trinidad.TT - Application des techniques C-13 à l'exploration du potentiel de séquestration du carbone des sols acides calcaires de Trinidad - Gouveia, Grégory (University of the West Indies (Saint-Augustine, Trinidad and Tobago), 2016)
Carbon dioxide (CO2) represents the largest proportion (74%) of total greenhouse gas (GHG) emissions globally, with agricultural activities accounting for about 25% of this gas. Opportunities to reduce emissions in the sector can therefore contribute significantly to the mitigation of global climate change. Ag-lime is widely used to mitigate soil acidity problems and the potential for this material to contribute to C sequestration in soils is of increasing interest to researchers. A laboratory experiment using C-13 isotopic labelling techniques was therefore established. The results established for the study showed significant differences (P<0.05) between the PMA estimates of the two techniques with the non-isotopic techniques giving higher estimates.